INTERVENSI ELEVASI KEPALA 30o PADA PASIEN PASCA OPERASI CRANIOTOMY SOL MENINGIOMA AREA FRONTALIS DENGAN CHARLES BONNET SYNDROME (CBS) DAN RIWAYAT PENGGUNAAN KONTRASEPSI: CASE REPORT - Meuthia Saulikha Triesna; Sandra Pebrianti; Nursiswati Nursiswati (SINERGI : Jurnal Riset Ilmiah, 2026)
Meningioma is an intracranial tumor of unknown etiology; however, progesterone is considered a hormonal factor associated with its incidence. Clinical manifestations include psychosis depending on the tumor location, with distinct symptoms such as the emergence of Charles Bonnet Syndrome (CBS). Additionally, Increased Intracranial Pressure (IICP) is a recurrent complication of craniotomy procedures. IICP poses a risk of cerebellar herniation, which can lead to decreased consciousness and respiratory arrest; therefore, intracranial management is crucial. One management strategy is 30° head elevation. This study aims to describe the application of a 30° head elevation intervention for decreased adaptive intracranial capacity in patient post-craniotomy for Space Occupying Lesion (SOL) Meningioma. This study utilized a case report design conducted in May 2023 at RSUD Sumedang. The results indicate that elevating the head above heart level facilitates venous return from the brain to the heart and helps activate the parasympathetic nervous system, which regulates bodily functions during rest. This maximizes patient relaxation, resulting in improved cerebral tissue perfusion, adequate oxygenation status, reduced headache, resolution of nausea and vomiting, and stable blood pressure. The 30° head elevation intervention is recommended as a non-pharmacological approach to address decreased adaptive     1     intracranial capacity, ensuring adequate cerebral blood circulation.